An Analysis Of Language Style Changing In Generation Z In Digital Communication On Whatsapp And Instagram (Case Study) At Politechnic Ganesha Medan, Campus 2 (4th Semester Students) - Selfitrida A. Yani; Fikri Najwan Arfi (Jurnal Warta Dharmawangsa, 2026)
This study looks into how Generation Z students' language usage has changed on digital communication platforms, particularly Instagram and WhatsApp. The study, which was carried out as a case study at Polytechnic Ganesha Campus 2, Medan, focused on the 32 participants in the fourth semester of class 24M24. The goal of the study is to identify the most common linguistic traits, linguistic deviation patterns, and sociolinguistic elements that affect language style changes in digital environments. Semi-structured interviews and a structured questionnaire were used in addition to direct observation of chat conversations and Instagram captions to obtain data. Code-switching, abbreviation, the use of slang and neologisms, phonological reduction, and the extensive use of emoji and visual symbols as linguistic tools are among the notable changes in language use that Generation Z students display, according to the research. WhatsApp serves as a semi-formal and casual communication tool, but Instagram tends to stimulate more creative and informal vocabulary. The study comes to the conclusion that Generation Z's language behavior is actively shaped and constantly changing by digital platforms, which has consequences for language instruction and academic communication standards.